Simple Fabrication of Porous 3D Substrate Polydimethylsiloxane (PDMS) Composited with Polyvinylidene Fluoride-co-Hexafluoropropylene (PVDF-HFP) for Triboelectric Nanogenerator - Phakkhananan Pakawanit; Utchawadee Pharino; Thitirat Charoonsuk; Saichon Sriphan; Satana Pongampai; Naratip Vittayakorn (Integrated ferroelectrics, 2021)
Owing to their structural advantages over bulk polymers, porous 3D substrates possess immense potential in triboelectric energy generation. This work reports the effective effort to fabricate the porous structure of polydimethylsiloxane, also known as the sponge-PDMS, by a simple template method. The sodium chloride salt from commodity product is used to create the 300 μm size of pores within the PDMS elastomeric layers, turning affects to the mechanical deformability of the triboelectric nanogenerator (TENG). The inner face of those pores is composited with the PVDF-HFP particles as a piezoelectric fillers. The presence of those fillers can be confirmed and their distribution within porous PDMS is 3D visualized by the synchrotron radiation X-ray tomography. The spatial distribution of the PVDF-HFP made it possible to fabricate the piezo-embedded macroporous TENG with high output power of 7.84 μW, giving over 2-fold enhancement, compared with the sponge-PDMS and even more when compared with the flat PDMS film under the same mechanical force.
Keywords: Advanced Sensor and Energy Harvesting Materials; Electrospun Nanofibers in Biomedical Applications; Tactile and Sensory Interactions